Sustainability of Tourism Development in the city of Ain-Sukhna, Egypt - Yasser Mahgoub (Alanya Hamdullah Emin Paşa Üniversitesi, 2022)
Tourism is a major economic source for Egypt, due to its significant natural and cultural attractions. Yet, rapid development and construction of touristic facilities have a negative impact on the fragile natural and cultural heritage. This paper studies the recent touristic developments of the coastal stretch of Ain-Sukhna on the Red Sea coastal region of Galala Mountain, and their impact on the surrounding natural and cultural attractions. Coral reefs and rich marine life have made this stretch among the prime fishing and scuba diving destinations in the world. The area is also famous for its year-round sunny beaches and the spectacular coastal scenic drive where Galala Mountain reaches the Red Sea. Recently, development has started on the mountains following the construction of Galala Mountain Road. Galala City started with Galala University and several residential, touristic, and commercial facilities. This paper studies the pattern of development in the area during the past 40 years and assesses its impact on natural and cultural resources.